The fiscal stability impact of monetary unions: looking beneath the Stability Pact debate - Philipp Paulus (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2004)
The discussion about the impact of a monetary union on the fiscal stability of individual member countries is largely confined to European Monetary Union and the Stability and Growth Pact (SGP) debate, which in turn tends to focus more on optimal fiscal rules. However, when adding insights from the theories of optimum currency areas, as well as from literature on fiscal stability analysis and exchange rate regimes in emerging markets, new layers are added to the discussion. Changes to the macroeconomic environment, changed incentives for fiscal authorities as well as possible changes in the reaction of capital markets are all factors that determine fiscal stability in a monetary union. This paper finds that some consequences of the institution of monetary union itself could alleviate the fear of heightened fiscal instability that is often assumed in the SGP debate. However, although the true nature of the problem of bailout for national fiscal authorities in a monetary union hinges likely less on the behaviour of fiscal authorities and more on the reaction of capital markets, this issue remains at the core of increased fiscal stability risk in a monetary union.
Keywords: H30; H63; F33; E63; 330; monetary union; fiscal stability; exchange rate regime; EU-Stabilitätspakt; Optimaler Währungsraum; Europäische Wirtschafts- und Währungsunion; Finanzpolitik; Internationale wirtschaftspolitische Koordination; Theorie